A Novel Miniaturized mmWave Antenna Sensor for Breast Tumor Detection and 5G Communication - Chinmoy Das; Mostafa Zaman Chowdhury; Yeong Min Jang (IEEE Access)
Breast cancer is one of the deadliest forms of disease that affects women worldwide. X-ray mammography, magnetic resonance imaging, and ultrasound are all helpful methods of medical imaging, but they have their own limitations due to low tissue contrast and side effects. Millimeter wave (mmWave) imaging has been offered as a viable alternative to the conventional screening methods due to their drawbacks. Without exposing the patient to ionizing radiations, malignant lesions can be detected by using the dielectric discontinuities in the tissues. The purpose of this work is to develop a simple, low-cost miniaturized mmWave imaging antenna sensor that can be used to detection of breast tumors or cancers in women by monitoring the changes in the antenna’s S11 parameter. The dimension of the proposed rectangular mmWave antenna is 5 mm $× $ 5 mm $×0.578$ mm. The proposed antenna sensor has an operating frequency band range of 32.626 GHz to 33.96 GHz with a peak gain of 6.65 dB and an efficiency of 91.46% in terms of radiation which makes it a suitable system for fifth generation (5G) communication. As well as the antenna sensor can detect very tiny malignant that size ≥1 mm inside the breast fantom.